Development of infrared radiation light source for integrated gas sensor - Tok, Jian Sheng (2018)
Over the years, miniature sensor based on Miro-electro-mechanical systems(MEMS) technology has evolved to a necessary item in places like hospitals, offices, security areas, power plants, etc. Therefore, the needs to come out with a better sensor model is ever increasing. In order to save electricity and the materials to fabricate the sensor, few elements will be commented in this report. This report aims to design and develop a MEMS emitter with high-efficiency Infrared Radiation for Integrated Gas Sensor applications. The MEMS emitter is with black platinum (Pt) coatings as emission material has a high emissivity (>95%) and good performance in reliability. It can be adopted by next generation low-power infrared gas sensor designs for varies of gas species and concentration detections. Simulation, modeling, fabrication and characterization are also included in this report.